National, collaborative evaluation of medical student and faculty perspectives on global surgery – Survey of undergraduate respondents on global surgery education (SURGE): A cross-sectional study. (September 2021) - ,; Kawka, Michal
Abstract: Introduction: It is estimated that 28–32% of the global burden of disease can be treated with surgery. Most of this burden is concentrated in low and middle-income countries, underpinning the importance of the topic of global surgery (GS). The multidisciplinary principles of GS are increasingly recognised as being key to modern practice and as such, must be fostered at early stages of medical training. However, it is unclear whether medical students are being exposed to GS. This study aimed to assess the importance of GS and its presence in medical curricula. Methods: A novel, 22-item online questionnaire was developed and disseminated to medical students and faculty members using social media platforms. Data collection was conducted by a collaboration of medical students, who acted as regional leads at their institutions. Results: 795 medical students and 141 faculty members representing 38/42 (90.4%) of UK medical schools completed the questionnaire. Only 84 students (10.6%) were previously exposed to GS. Most students (66.3%) and faculty (60.6%) agreed that GS should be an integral part of the curriculum. Only 20 students (2.5%) were familiar with what a career in GS means. Conclusion: Approximately two-third of students and faculty agree that global surgery should be an integral part of the mandatory curriculum. Findings of this study should underpin further incorporation of GS into curricula, as high-income countries can decisively contribute to achieving the global surgery 2030 targets, by training a new generation of clinicians who are ready for the challenges of the 21st century. Highlights: Global surgery is perceived as lacking in curricula, despite ample interest from medical students. Key topics in global surgery topics should be integrated into mandatory teaching. Exposure to global surgery is associated with greater knowledge and career understanding.